The Influence of Digital Media and Brands On Children’s Behavior - Tabone, Flávia Melo Muniz; Lopes, Evandro Luiz; Carvalho, Joana Rosa Cardoso de; Cavalcante, Pedro Paulo Santos (Revista Interdisciplinar de Marketing, 2025)
This study investigates the influence that digital social media and brands have on the behavior of children aged 4 to 9. The research, qualitative and exploratory in nature, was conducted through relaxed interviews with ten children, organized in a game format to encourage authentic reactions. The results indicate that even very young children are deeply impacted by advertising, often unconsciously. Moreover, it was found that parents are not fully aware of the extent of this media influence and tend to believe its effects are limited to excessive consumption, overlooking other potential consequences. From an academic perspective, the study broadens the understanding of the impacts of marketing strategies targeting children, providing valuable insights for future research on child consumer behavior and brand relationships. In practical terms, the findings highlight the importance of greater vigilance on the part of parents, schools, and regulators regarding children’s use of digital media. By doing so, it becomes possible to foster more informed and healthier young consumers, minimizing excessive exposure to advertising and its potential negative repercussions on child development.